2006
DOI: 10.1149/1.2165709
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Ru-Ir Nanoparticles Prepared by Vapor Deposition as a Very Efficient Anode Catalyst for Methanol Fuel Cells

Abstract: Preparation of Pt-Ru-Ir nanoparticle catalysts on carbon black by a novel vapor deposition method is reported. Particle size as assessed by transmission electron microscopy is ca. 2.5 nm with narrow distribution. Moreover, they are homogeneously dispersed on the substrate. The electrocatalytic activity of the particles toward methanol electro-oxidation was investigated by cyclic voltammetry, chronoamperometry at constant potential, and adsorbed CO-stripping voltammetry. It was found that these catalysts posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…It is known that along with Ru and Sn, Ir also activates and promotes the electro-oxidation of adsorbed CO-like species, as seen in DEFC [19] and DMFC [20,21]. de Tacconi et al [22] investigated ethanol oxidation on Ir and Rh electrodes by the FTIR method, and they found that electro-oxidation of ethanol on Ir is selective and produces mainly acetic acid, while on Rh it produces CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that along with Ru and Sn, Ir also activates and promotes the electro-oxidation of adsorbed CO-like species, as seen in DEFC [19] and DMFC [20,21]. de Tacconi et al [22] investigated ethanol oxidation on Ir and Rh electrodes by the FTIR method, and they found that electro-oxidation of ethanol on Ir is selective and produces mainly acetic acid, while on Rh it produces CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent cooling of the chamber results in deposition of the metal clusters onto the substrate surface. Then the precursor impregnated substrate is kept at high temperature (~300 °C) under nitrogen atmosphere to decompose and yield PtRu bimetallic nanoparticles [61]. In plasma sputtering method, Pt and Ru targets are faced to the substrate (carbon support) at a specific distance, in a vacuum chamber.…”
Section: Preparation Of Pt-based Catalysts On Cnmsmentioning
confidence: 99%
“…Moreover, these catalysts also exhibit excellent performance in the electrocatalysis of methanol in direct methanol fuel cells (DMFCs). 22, 23 Chen et al 24 showed that a thin layer of IrO 2 on Ti/IrO 2 /Pt improved the activity of these electrodes for methanol electrooxidation. They demonstrated that the current density increased and that the onset potential for methanol electrooxidation also shifted over 200 mV downward compared to the Ti/Pt nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, IrO 2 is extensively used in the preparation of mixed oxide electrodes, and numerous reports have suggested the application of Ir and its oxides in fuel cell systems. 22,[27][28][29] Indeed, results obtained through in situ Fourier transform infrared (FTIR) studies for ethanol electrooxidation on Ir electrodes 30 (Pt electrodes containing some Ir or its oxides and quaternary electrocatalysts) showed that these systems perform well for ethanol oxidation in a direct ethanol fuel cell.Considering these results, it is evident that the presence of Ir in the electrocatalyst has a synergetic effect (generally with Pt) for both ethanol oxidation and direct ethanol fuel cell performance. Therefore, the aim of this work is to produce an optimized PtSnIr/C electrocatalyst, prepared by polymeric precursor method, to be used for both ethanol oxidation and as anode in a direct ethanol fuel cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation